Review and analysis of empirical articles published in TESOL Quarterly over its lifespan - A. Mehdi Riazi (19438264) (2023)
We report the results of a bibliometric study of 696 empirical articles (EAs) published in TESOL Quarterly (TQ) over its lifespan (1967-2019). We report overall and periodic reviews (1967-1979, 1980-1989, 1990-1999, 2000-2009, 2010-2019) concerning the following themes: (1) contexts and participants, (2) research foci and theoretical orientations, and (3) research methodology and data sources. A typical article was written by a single author addressing a learning/teaching English issue related to undergraduates in US universities. The most common research foci were instruction, learning, and assessment. A quarter of the articles did not have a specifiable theoretical orientation, and for those that had, the main theoretical orientations were linguistic/scientific, linguistic/cognitive, and social. The most frequently used research methodologies were quantitative, qualitative, and eclectic, and the top three data sources used by researchers were elicitation, multiple sources, and observation. Based on the findings, we make suggestions for future research in TESOL. Overall, the present review and analysis of published EAs give readers a birds-eye view of the research gravity in TQ over the last 52 years. Other Information Published in: Studies in Second Language Learning and Teaching License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.14746/ssllt.40217